Effect of synthetic method on CeZr support and catalytic activity of related Rh catalyst in the oxidative reforming reaction. Issue 1 (January 2019) - Basile, F.; Mafessanti, R.; Fasolini, A.; Fornasari, G.; Lombardi, E.; Vaccari, A.
Abstract: The production of hydrogen by oxy-reforming is a process coupling steam reforming and catalytic partial oxidation allowing a balance of endothermic and exothermic reaction and smoothing the temperature profile. Nevertheless, deactivation of the catalyst by carbon formation is still an issue favored by low O/C and Steam/C ratio used in the process. The development of a catalyst for the oxy-reforming process started with the study of the synthesis by water-in-oil microemulsion of Ce0.5 Zr0.5 O2, to obtain high oxygen storage capacity, a property that helps the removal of eventually formed carbon. The studied synthesis was able to provide the desired Ce0.5 Zr0.5 O2 with a good stability with temperature, while classical coprecipitation gives Ce0.6 Zr0.4 O2 phase. The catalysts were impregnated with 2.7% of Rh and tested in oxy-reforming using low residence time and reaction conditions able to discriminate the differences in catalyst activity. The catalyst prepared using microemulsion CeZr showed higher conversion and stability when compared with the one synthesized by coprecipitation. In particular, differently from the coprecipitated sample, the carbon formation was not present in the one prepared by microemulsion. The activity and stability were linked to the characterization features of the mixed oxides and the impregnated catalysts.